Multidisciplinary approach to cardiac and pulmonary vascular disease risk assessment in liver transplantation: An evaluation of the evidence and consensus recommendations. Issue 1 (18th November 2017) - VanWagner, Lisa B.; Harinstein, Matthew E.; Runo, James R.; Darling, Christopher; Serper, Marina; Hall, Shelley; Kobashigawa, Jon A.; Hammel, Laura L.
Abstract : Liver transplant (LT) candidates today are older, have greater medical severity of illness, and have more cardiovascular comorbidities than ever before. In addition, there are specific cardiovascular responses in cirrhosis that can be detrimental to the LT candidate. Cirrhotic cardiomyopathy, a condition characterized by increased cardiac output and a reduced ventricular response to stress, is present in up to 30% of patients with cirrhosis, thus challenging perioperative management. Current noninvasive tests that assess for subclinical coronary and myocardial disease have low sensitivity, and altered hemodynamics during the LT surgery can unmask latent cardiovascular disease either intraoperatively or in the immediate postoperative period. Therefore, this review, assembled by a group of multidisciplinary experts in the field and endorsed by the American Society of Transplantation Liver and Intestine and Thoracic and Critical Care Communities of Practice, provides a critical assessment of the diagnosis of cardiac and pulmonary vascular disease and interventions aimed at managing these conditions in LT candidates. Key points and practice‐based recommendations for the diagnosis and management of cardiac and pulmonary vascular disease in this population are provided to offer guidance for clinicians and identify gaps in knowledge for future investigations. Abstract : In this white paper, the American Society of Transplantation Liver and Intestinal and Thoracic and Critical Care Communities of Practice summarize current evidence and make consensus recommendations for cardiac and pulmonary vascular disease risk assessment for potential liver transplant recipients.